Apical versus subclavian transcatheter aortic valve implantation: An 8‐year United Kingdom analysis. Issue 4 (11th February 2022) - D'Auria, Francesca; Santo, Danilo F.; Myat, Aung; Lorusso, Roberto; Ravaux, Justine M.; Trivedi, Uday; Hildick‐Smith, David
Abstract: Objectives: Subclavian (SC) and transapical (TA) approaches are the main alternatives to the default femoral delivery for transcatheter aortic valve implantation (TAVI). The aim of this study was to compare complications and morbidity/mortality associated with SC and TA in a long‐term time frame. Methods: From January 2007 to July 2015, 1506 patients underwent TAVI surgery in 36 United Kingdom TAVI centers. Primary outcomes were complications according to VARC‐2 criteria. The secondary outcome was long‐term survival. Results: The enrolled patients were distributed as follows: 1216 in the TA group and 290 in the SC group. There were no differences in the rates of acute myocardial infarction, emergency valve‐in‐valve, paravalvular leak, balloon post dilatation, cardiac tamponade, stroke, renal replacement therapy, vascular injuries, and 30‐day mortality among the groups. Conversely, the rate of permanent pacemaker implantation ( p  = .02), the procedural time duration ( p  = .04), and the 12‐month mortality ( p  = .03) was higher in SC than in TA, while in‐hospital length of stay was reduced in SC than in TA ( p  = .01). Up to 8 years, the long‐term mortality was not different among groups ( p  = .77), and no difference in long‐term survival between self‐ versus balloon‐expandable devices was found ( p  = .26). Conclusions: According to our results, TA provided the best 12‐month survival compared to SC, while the long‐term survival up to 2900 days is not significantly different between groups, so SC and TA may both represent a safe non‐femoral access if femoral is precluded.